Probiotic-based nanoparticles for targeted microbiota modulation and immune restoration in bacterial pneumonia. Issue 2 (16th October 2022) - Fu, Jieni; Liu, Xiangmei; Cui, Zhenduo; Zheng, Yufeng; Jiang, Hui; Zhang, Yu; Li, Zhaoyang; Liang, Yanqin; Zhu, Shengli; Chu, Paul K; Yeung, Kelvin Wai Kwok; Wu, Shuilin
ABSTRACT: While conventional bacterial pneumonia mainly centralizes avoidance of bacterial colonization, it remains unclear how to restore the host immunity for hyperactive immunocompetent primary and immunocompromised secondary bacterial pneumonia. Here, probiotic-based nanoparticles of OASCLR were formed by coating chitosan, hyaluronic acid and ononin on living Lactobacillus rhamnosus . OASCLR nanoparticles could effectively kill various clinic common pathogens and antibacterial efficiency was >99.97%. Importantly, OASCLR could modulate lung microbiota, increasing the overall richness and diversity of microbiota by decreasing pathogens and increasing probiotic and commensal bacteria. Additionally, OASCLR could target inflammatory macrophages by the interaction of OASCLR with the macrophage binding site of CD44 and alleviate overactive immune responses for hyperactive immunocompetent pneumonia. Surprisingly, OASCLR could break the state of the macrophage's poor phagocytic ability by upregulating the expression of the extracellular matrix assembly, immune activation and fibroblast activation in immunocompromised pneumonia. The macrophage's phagocytic ability was increased from 2.61% to 12.3%. Our work provides a potential strategy for hyperactive immunocompetent primary and immunocompromised secondary bacterial pneumonia. Abstract : The probiotic-based nanoparticles could effectively treat immunocompetent primary and immunocompromised secondary bacterial pneumonia by restoring host immunity.